Elements of theory of elasticity: study aid - Svetashkov A. A. Aleksandr Andreevich; Kupriyanov N. A. Nikolay Amvrosievich; Pavlov M. S. Mikhail Sergeevich; Manabaev K. K. Kairat Kamitovich (Tomsk, TPU Publishing House, 2024)
Текст на английском языке